Power measurement to assess the useful strength in BMX cycling - Mateo, M.; Zabala, M.; Blasco, C.; Velarde, S.; Garrido, R.; Oviedo, A.; Simon, A. (Archivos de medicina del deporte, 2008)
It`s very important to know the different factors that determine performance in Bicycle Moto Cross (BMX) discipline. Although technique has been more described, it`s still unknown the type of strength that is used specifically in BMX competitions. Methods: In this study we have measured the strength used in BMX tracks by means of the PowerTap powerm eter (PT) in a sample of 26 cyclists (20 of them of the Spanish national team, and 6 national top level). A wide range of tests were developed consisting in: 1) fi rst straight line (FL), 2) 90 meters sprint (90m), 3) maximal intensity of competition lap (CT); the last one in 3 different tracks. The power, time to peak power, and mean power were measured in each repetition of each subject. Values of power (watts), acceleration time (s), acceleration angle a, and maximal Rate of Force Development (RFDmáx) were measured using the method of triangulation of curves force/time. Results: For the test (1) the average values were: acceleration time (FL- 1.5 ±0.28 s, 90m- 3.24 ±0.67 s, CT- 1.64 ±0.39 s); peak power (FL- 1052.88 ±169.69 watts, 90m- 1343.2 ±198.64 watts, CT- 1159.43 ±112.17 watts), acceleration angle a is (FL- 89.91 ±0.01°, 90m- 89.86 ±0.05°, CT- 89.91 ±0.02°,), and RFDmáx. is (FL- 712.77 ±107.22 watts • s-1, 90m- 447.01 ±137.07 watts • s-1, CT- 800.51 ±131.66 watts • s-1). By the way, PT registers one data for each 1.26 seconds, so we don`t know when peaks of power appear and we can`t measure RFD (Figure 1). Conclusion: The PT can be useful to quantify and compare different trainings, but it doesn`t allow us to analyze accurately the peak power and RFD to assess the useful strength in BMX. More accurate tools need to be developed measuring in higher frequencies.